Hedges and Boosters in Indonesian Thesis and Dissertation Abstracts - Septiani, Rifanny Zahra; Kurniawan, Eri (RETORIKA: Jurnal Ilmu Bahasa, 2025)
The effective expression of arguments in academic writing is largely shaped by rhetorical strategies, particularly hedges and boosters, which aid in managing certainty and engagement. This study employs a qualitative design with a corpus-based approach, utilizing 144 abstracts from bachelor's theses, master's theses, and doctoral dissertations in Indonesian language education. The abstracts were extracted, converted to text format, and organized into three corpora based on academic level. Using AntConc 4.1.4, softening and strengthening words were identified based on Hyland's (2005) grammatical classification and Hyland's (1998) pragmatic framework. The analysis included the identification of lexical words, calculation of their frequency, and interpretation of their use at various academic levels. To ensure validity, selected examples were analyzed qualitatively to reveal patterns of metadiscursive strategy use by students when presenting scientific claims. The findings indicate undergraduate and master's students primarily use hedges, particularly modal verbs like "can", "could", and "may" to express cautious claims, while doctoral students more frequently use boosters, especially lexical verbs such as "prove", "show", and "assert", reflecting greater assertiveness and confidence. Pragmatic analysis reveals that both hedges and boosters serve mainly accuracy- and writer-oriented functions, with limited reader-oriented use. These results suggest a rhetorical shift from cautious to assertive claims in line with academic maturity. The study highlights fostering students’ awareness of rhetorical strategies for effective scientific communication.